367 Improving Handover Documentation in Surgical Inpatients Using Weekend Handover Stickers. (4th May 2021) - Boyle, C; Chien, S; McCallum, A
Abstract: Introduction: Transfer to the care to the oncoming team is the point at which inpatients are most vulnerable. Effective handover is vital to protect patient safety and clinical governance. The Royal College of Surgery (RCS) Safe Handover guidelines highlight relevant information required for comprehensive handover. This QI project aimed to determine if implementation of weekend handover stickers in surgical patients' notes improved handover documentation. Method: A retrospective records-based audit of patients admitted under general surgery over a 4-week period was performed. Standards were set using the RCS guidelines to determine if sufficient weekend handover was documented. We designed weekend handover stickers to be inserted in notes based on guidelines. A re-audit cycle over a 4-week period was performed to determine if the intervention improved handover documentation. Results: 119 patients were in the initial audit. 125 patients were in the re-audit. Documented handover in the notes improved from 43.7% to 89.6% after intervention. Documentation of the following clinical information also improved: clinical situation (43.7% to 92.0%); co-morbidities (14.3% to 89.6%); current issues (71.4% to 94.4%); weekend blood tests (32.8% to 92.0%); antibiotic therapy (21.8% to 92.0%). Conclusions: Weekend handover stickers resulted in a significant improvement in handover documentation improving patient safety.